PO201 A survey on employment in charcot-marie-tooth disease in UK. (1st December 2017) - Withers, Tristan; Laura, Matilde; Skorupinska, Mariola; Bull, Karen; Butcher, Karen; Reilly, Mary M
Abstract : Charcot-Marie-Tooth disease (CMT) is the most common inherited neuropathy. Many CMT patients become gradually less able to perform physically demanding tasks as their disease progresses. In collaboration with the charity Charcot Marie Tooth UK (CMTUK) we designed an online survey to determine the effect of CMT on a person's ability to find and perform work, and to maintain their job. Retired participants answered questions regarding their age of retirement and their decision to retire. Over a 12 month period, 301 responses were received. Participants came from across the UK and from a wide variety of occupations. 77% of participants felt that CMT affected their ability to work, 60% of participants felt that CMT had restricted them from finding work and 25% of respondents were forced to change career because of CMT. 45% of participants were retired and only 6% retired after the age of 65. 57% of participants retired early because of CMT. Our findings show that CMT affects patients' career choices, their ability to work and is a common reason for early retirement. This raises important questions about how society needs to evolve processes to help people with CMT and similar diseases work and stay at work.